A substance with negative mass - BG Golovkin (Annals of Mathematics and Physics - Peertechz Publications, 2023)
The conditions for the formation of a substance with a negative mass are investigated. The critical velocity of a body ω = 235696.8871 km/s, necessary for its transition to a massless state, was determined by two independent methods. Zeroing of the mass of matter also occurs at a temperature T =2.17 . 1036 mo  (mo is the rest mass of the particle in grams). At higher temperatures or speeds of movement, the mass of bodies becomes negative. The resulting formulas made it possible to calculate the masses of X,Y-bosons equal to 4.606 . 10-9 g. The temperature of the Superunification of the four fundamental interactions, including gravity, is estimated to be 4.72 . 1031 K.